Customer-Classified Intracity Fruit Distribution Path Optimization: A Case Study in Jining, China - Huiyi, Pang; Qianyi, Wang; Yiding, Zhao (International Journal of Emerging Trends in Social Sciences, 2021)
With the development of technology and economy, customer satisfaction is becoming increasingly important to businesses. Customers expect more in regard to product quality, personalised service and delivery date. This study randomly selected customers from a small-to-medium sized company in China as case study and used a K-Means cluster analysis approach to present the available management in logistics. The mileage saving method was also used to contribute the distribution path planning. This resulted in a more scientific distribution route based on comparative analysis, which helped the target company save resources and improve efficiency. This study helped companies effectively identify customer value by combining customer classification with intracity distribution path optimization. Simultaneously, it provides possible empirical reference to service quality improvement, the distribution path optimization, the resource wasting reduction and the companies’ operation efficiency enhancement. It enriches the current literature about food distribution path optimization for small and medium sized food company.